2020
DOI: 10.1177/0193945920918334
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Culturally Tailored Interventions for Chronic Illnesses among Ethnic Minorities

Abstract: Culturally tailored interventions have been applied to provide benefits to ethnic minorities’ care; however, the effectiveness of these interventions for chronic conditions is mixed. This systematic review of systematic reviews critically evaluates recent evidence of the effects that culturally tailored interventions have on health care outcomes among ethnic minorities with chronic conditions. It synthesizes results of eight English-language systematic reviews published between 2010 and 2018 and identifies fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In contrast to Attridge et al (2014) who reported sustained improvement up to 24 months of follow-up, this review found short-term improvement prevalent up to 8 months (19) , but these effects on glycaemic control did not persist significantly at 12 or 24 months. A recent systematic review reported findings that the use of culturally tailored interventions for chronic disease management contributed to improvement in all healthcare outcomes, but that overall results were mixed (38) . This outcome was seen in our study, where six articles reported non-significant improvement in HbA1c for the intervention compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Attridge et al (2014) who reported sustained improvement up to 24 months of follow-up, this review found short-term improvement prevalent up to 8 months (19) , but these effects on glycaemic control did not persist significantly at 12 or 24 months. A recent systematic review reported findings that the use of culturally tailored interventions for chronic disease management contributed to improvement in all healthcare outcomes, but that overall results were mixed (38) . This outcome was seen in our study, where six articles reported non-significant improvement in HbA1c for the intervention compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that the lack of practical guidelines were obstacles for healthcare providers (Coleman & Angosta, 2017 ; Ogbolu et al, 2018 ). Similarly, several studies reported that a lack of clinical practical guidelines for culturally competent care (Joo & Liu, 2020 ; Marion et al 2016 ). Clear, evidence‐based practical manuals are needed to improve the practices of nurses and other healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the evidence of intervention dosage and connecting that evidence to patients' outcomes can improve the overall evidence base of research and ensure high quality of health care (Sidani et al, 2010). However, studies in this review reported that lack of process measuring was a barrier (Alia et al 2015;Allen et al 2019;Gonyea et al, 2016;Huang & Garcia, 2018;Joo & Liu, 2020). Developing reliable and validated tools to measure culturally tailored interventions is therefore recommended.…”
Section: Implications For Researchmentioning
confidence: 99%
See 2 more Smart Citations